Natural sweetener agave inhibits gastric emptying in rats by a cholecystokinin-2-and glucagon like peptide-1 receptor-dependent mechanism - YEGEN, BERRAK; ÖZBEYLİ, DİLEK; BAYRAKTAR, SEZİN (ROYAL SOC CHEMISTRY, 2017)
Low-calorie sweeteners are considered to be beneficial in calorie control, but the impact of these sweeteners on gastric emptying is not well described. The purpose of this study was to compare the gastric emptying rate of agave nectar with those of glucose and fructose, and to evaluate the interaction of cholecystokinin (CCK)-1, CCK-2 and glucagon-like peptide-1 (GLP-1) receptors in agave-induced alterations in gastric emptying. Female Sprague-Dawley rats were fitted with gastric cannulas. Following the recovery, the gastric emptying rates of glucose, fructose and agave at 12.5%, 15% or 50% concentrations were measured and compared with that of saline. GLP-1 receptor antagonist exendin fragment 9-39 (30 mu g kg(-1)), CCK-1 receptor antagonist devazepide (1 mg kg(-1)) or gastrin/CCK-2 receptor antagonist YM022 (1 mg kg(-1)) was injected subcutaneously 1 min before the emptying of glucose, fructose or agave at their 50% concentrations. When compared with saline emptying, gastric emptying of glucose was significantly delayed at its 25% and 50% concentrations, but the emptying of 12.5% glucose was not different from that of saline. Agave emptying, which was delayed with respect to saline emptying, was not altered by CCK-1 receptor blockade; but agave emptied from the stomach as rapidly as saline following the blockade of either CCK-2 or GLP-1 receptors. The findings demonstrate that the inhibitory effect of agave on gastric emptying is mediated by both CCK-2 and GLP-1 receptors, suggesting that natural sweeteners including agave may have satiating effects through the inhibition of gastric motility via enteroendocrine mechanisms.
Keywords: LOW-CALORIE SWEETENERS; FOOD-INTAKE; NONNUTRITIVE SWEETENERS; GUT FUNCTION; WEIGHT-GAIN; BODY-WEIGHT; SATIETY; GLP-1; CCK; GLUCOSE